Structure-based virtual screening of Philippine natural products to discover novel inhibitors against mycobacterium leprae MurE ligase - Hsiao, Vivien B. (Animo Repository, 2026)
The emergence of drug-resistant strain in the causative agent of leprosy, Mycobacterium leprae, propels the need to find a cure and new antibacterial targets. Cytoplasmic Mur ligase enzymes involved in peptidoglycan biosynthesis have recently been reassessed as attractive targets for antibiotics, as they are distinct to bacteria. This work aimed to characterize and model the M. leprae ATP-dependent MurE ligase protein structure and computationally identify potential antibacterial agents against this target. To do this, sequence alignment and residue conservation analysis were carried out, followed by homology modeling of MurE, docking studies, molecular dynamic simulations, and network analysis. The reliable homology model of the MurE protein was used to dock all the ADME screened ligands from the Philippine natural products for the identification of the top three docking hits, namely alpha-cadinene (C1), cis-b-guaiene (C2), and seychellene (C3). The native ligand (ATP) and products (ADP) were also docked to observe the behavior of the protein with respect to its original catalytic activity. Results showed that M. leprae MurE contains 3 conserved domains, in which the study focused on the central domain (D2) and the highly conserved residues and GKT motif for ATP binding. Molecular dynamics (MD) were then performed on the apo and the bound structures to analyze protein behavior upon ligand binding, and to confirm and compare the stability of the liganded complexes. MD analysis revealed structural domain-based movements of the protein upon ligand binding with a rigid binding pocket consisting of the identified binding residues and essential decomposition residues from interaction and decomposition analysis, respectively. Binding free energy analysis established the favorable binding affinity of the substrate and inhibitors to the protein, contrary to the unfavorable binding of the product. Lastly, network analysis identified key residues for each complex that signify crucial transmission points with a proposed role in both ligand binding and communication within the protein. Although, there are potential areas for future studies, such as the identified potential allosteric site of the C1 ligand, application of principal component analysis (PCA) on the MurE protein, and longer MD simulations and trajectory analysis for all the complexes for more deliberations and observations.